Long-Term Mortality of Stroke Survivors in Parakou: 5-Year Follow-Up. - Houinato, Dismand (My University, 2020)
Background: The burden of stroke is high in Africa, but few data are available on the long-term outcome of strokes in this area. Aim: We aimed to study the long-term outcome of stroke survivors in Parakou from 2012 to 2018. Methods of study: It was a cohort study and included 247 stroke patients admitted to the University Hospital of Parakou from January 1, 2012 to April 30, 2018. Each patient was followed up for at least 1 year. The modified RANKIN scale was used to evaluate patients. Verbal autopsy was used to ascertain the cause of death. The survival probability was estimated using the Kaplan-Meier method. Predictors of mortality were estimated using the Cox proportional model and the hazard ratio (HR) and their 95% confidence intervals were determined. The data were analyzed using Stata Software. Results: The mean age was 58.1 ± 13.4 years with a sex ratio of 1.12. Among stroke survivors, the mortality was 10.1% at 3 months, 11.7% at 6 months, 15.4% at 1 year, 21.5% at 3 years, and 23.5% at 5 years. The probability of survival after a stroke was 66.5% at 5 years. Factors associated with mortality were age with adjusted HR 1.4 (1.2-1.7) for each 10 years, male sex with aHR 2.3 (1.2-4.6), history of hypertension with aHR 2.0 (1.0-4.1) and the severity of the initial neurological impairment National Institute of Health Stroke Scale with aHR 1.1 (1.0-1.2) for each 1 point. The main causes of death were recurrent stroke, infectious diseases, and cardiac disease. The proportion of patients with functional disability was 53.8% at 1 year. The quality of life was generally impaired in terms of physical health, personal environment, and finances. Conclusions: The long-term prognosis of stroke patients in Parakou is poor. It requires urgent action to reduce this burden.
Keywords: Africa; Stroke; long-term mortality; outcome